Encapsulated butyric acid and bacillus subtilis as antibiotic substitutes to mitigate heat stress and promote gut health and perfomance in broilers - Jansen van Rensburg, Christine (University of Pretoria, 2020)
Dissertation (MSc (Agric))--University of Pretoria, 2019.